Evaluation of PJOK Learning In Sman I Karangan Trenggalek - Via Diah Rohmana; I Made Sriundy Mahardika; Abdul Rachman Syam Tuasikal (BIRCU, 2019)
The purpose of this study was to determine the implementation of physical education, sport, and health (PJOK) learning in SMAN I Karangan Trenggalek using the CIPP model (context, input, process, product) developed by Stufflebeam. Evaluation research uses a mix analysis method. Sources of research data are Physical Education Teachers, representatives of the curriculum, as well as Principals who are in SMA Negeri 1 Karangan Trenggalek. Primary data collection uses observation instruments while secondary data is obtained through documentation and interviews. Data obtained from observations were then analyzed quantitatively while data from documentation and interviews were analyzed descriptively qualitatively. From the results of research conducted showed that the implementation of PJOK learning programs in SMAN I Karangan Trenggalek included in the very good category.